Analisis Pengaruh Likuiditas, Solvabilitas, dan Profitabilitas Terhadap Harga Saham - Marpaung, Bintang Sahala M; Hasibuan, David HM; Marpaung, Annaria Magdalena; Anwar, Chyntia Novalita (Jurnal Ekonomi Bisnis, Manajemen dan Akuntansi (Jebma), 2024)
This study aims to determine the effect of liquidity, solvency, and profitability on the stock prices of trading companies listed on the Indonesia Stock Exchange for the 2017-2021 period. This study uses a quantitative approach. The sample in this study was taken using the purposive sampling method from trading companies listed on the Indonesia Stock Exchange during five years 2017-2021, initially 79 companies were narrowed down to 8 trading companies where the company's financial reports are available and accessible to the public. The results of this study are: (1) Current Ratio (CR) has no significant effect on stock prices with a significance value of 0.200 > 0.05. (2) Debt to Equity Ratio (DER) has a significant effect on stock prices with a significance value of 0.002 <0.05. (3) Return on Equity Ratio (ROE) has a significant positive effect on stock prices with a significance of 0.005 <0.05. Based on the results of simultaneous testing, this study was able to prove that there was a significant influence between the Current Ratio (CR) Debt to Equity Ratio (DER) and Return on Equity (ROE) variables on stock prices.